Fenomenologi Trauma Geriatric di Kota Padang - Mariza Elsi; Dian Rahmi; Anisa Febristi (Sarana Ilmu Indonesia (salnesia), 2021)
In almost every developed country, the proportion of people aged over 60 years is growing faster than other age groups, judging from the biological aspect of the elderly belonging to age with an aging process characterized by decreased physical endurance, researchers claim that every individual over 65 years old has experienced falls once a year. The purpose of this study was to explore the experiences of the elderly who have experienced trauma or falls and what they expect using the interpretative phenomenology method carried out in the city of Padang. The selection of participants by randomly selecting areas in the scope of the city of Padang as many as 6 participants who fall into the category of elderly according to WHO. Data collection through interviews used open-ended interviews with semi-structured questions for 30-60 minutes. Interviews were recorded with a voice recorder and field notes were used to record things that could not be recorded. Five themes had been identified, among others, the description of the elderly's feelings about the decline in physical condition, the circumstances that cause falls, the main treatment in the event of trauma/falls, the ability to condition repeated falls, the availability of health services for the elderly. The conclusions of the themes that have been found show that health workers need to provide special services to the elderly who experience decreased function and realize that the elderly who have experienced trauma have limitations and difficulties due to physical incapacity so that they require prevention and health promotion so that repeated trauma can be avoided.